Real-World Data on Apatinib Efficacy - Results of a Retrospective Study in Metastatic Breast Cancer Patients Pretreated With Multiline Treatment - Liu, Zhaoyun; Shan, Jing; Yu, Qian; Wang, Xinzhao; Song, Xiang; Wang, Fukai; Li, Chao; Yu, Zhiyong; Yu, Jinming (Frontiers in Oncology, 2021)
Objectives: The NCCN guidelines recommend that the addition of bevacizumab should be considered in metastatic breast cancers in some circumstances, but there are no recommendations for the similar antiangiogenic drug apatinib. The aim of this study was to evaluate the safety and efficacy of apatinib in metastatic breast cancer patients pretreated with multiline treatment in a real-world setting. Materials and Methods: Metastatic breast cancer patients pretreated with multiline treatment who had apatinib treatment initiated from September 2015 to August 2019 at Shandong Cancer Hospital and Institute were included. The primary endpoints included PFS and OS, and the secondary endpoint was treatment-related toxicity. Results: A total of 66 patients with metastatic breast cancer received apatinib treatment after failure of multiline chemotherapy in this study. The median PFS and OS of all 66 patients were 6.0 months and 10.0 months, respectively. The clinical beneficial rate was 40.9%. All patients tolerated treatment well, and no patients died of toxicity. The common toxicities of apatinib were hand and foot syndrome, secondary hypertension and fatigue events. The number of prior chemotherapy regimens was significantly associated with DFS and OS. Capecitabine may be a better choice for apatinib with a longer OS of 19 months, while apatinib combined with other drugs was 9 months, and the apatinib monotherapy was 10 months. Conclusion: Apatinib produced moderate efficacy in metastatic breast cancer patients pretreated with multiline treatment with no significant treatment-related adverse events. Apatinib might be a choice for women as a maintenance salvage therapy following multiline chemotherapy failure.